Advances in the knowledge and treatment of dyslipoproteinemias - Garmendia, Fausto (2003)
A review of the lipidic and non-lipidic cardiovascular risk factors is done. The increase of LDL, VLDL, IDL cholesterol, non-HDL triglycerides and lipoprotein(a) as well as HDL cholesterol decrease were considered as main lipidic cardiovascular risk factors. Dyslipoproteinemias are classified as primary and secondary. Primary dyslipoproteinemias are inborn errors of lipid metabolism, familiar or non-familiar, including common hypercholesterolemia, combined familiar hyperlipidemia, familiar hypercholesterolemia, familiar hypertrigliceridemia, VLDL remanents hyperlipidemia and primary quilomicronemia. The secondary dyslipoproteinemias are produced by various diseases, including hypotiroidism, diabetes mellitus, nephrotic syndrome, chronic biliary obstruction, renal insufficiency and so on; there are some drugs that modify lipid metabolism such as alcohol, beta-blockers, diuretics, progestagens, corticosteroides, and many others. It is emphasized that the fasting lipid profile alone is not sufficient to determine the lipidic metabolic disorder, and it is suggested the convenience of conducting postprandial studies. In the therapeutic handling it is necessary to consider the diet and physical exercises; and when these measures are not sufficient, try to normalize the lipid profile by using drugs such as hydroxi-metil-glutaryl coenzime A inhibitors and fibric acids derivatives. Therapeutic interventions, supported by results of multicentric international mega-studies, have shown a decrease in the prevalence of the cardiovascular events and the related morbidity and mortality.